Media Dissemination of Smart Cabinets at RA AL Kholafiyah Brani Kulon Maron Probolinggo - Rofikha Nuriyanti; Ludfi Arya Wardana; Ulfi Kurniawati; Ni Putu Ayu Cahaya Putri; Asfia Innisya (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
The problem that occurs in schools is that the real condition is learning in TK/RA children. Learning media is not complete and there is no visual form of learning media that can be used to develop the cognitive aspects of students. This is because seen from the characteristics of the material it requires a visual explanation in the form of a stationary object but can be used as an innovative learning medium. In addition, printed books are considered less motivating and increase the attractiveness of students in learning so that learning outcomes cannot be maximized. From these problems, the ideal condition to be achieved is the need to develop a learning media in the form of interactive and innovative media that can provide knowledge to students. With interesting media, it is hoped that it can increase motivation, the attractiveness of students to learn so that it can improve student learning outcomes.